Bridging Faith and Finance: A Comparative Analysis of Islamic Bank Resilience and Contagion Risk During Global Economic Shocks (2008 vs. 2020 Crises) - Samsul, Effendi; Agustami, Eli (PT Inovasi Pratama Internasional, 2026)
This study investigates the comparative resilience and contagion risk profiles of Islamic banking systems during two major global economic crises: the 2008 Global Financial Crisis (GFC) and the 2020 COVID-19 pandemic. . However, profitability declined significantly in 2009 when the crisis affected the real economy. Conversely, during the COVID-19 pandemic, Islamic banks exhibited comparable systemic vulnerabilities to conventional banks when facing exogenous shocks, though with significantly reduced spillover effects. CAR increased from 24.0% to 26.5% while NPF improved from 2.1% to 2.0% during COVID-19, demonstrating structural resilience despite ROA declining from 1.9% to 1.4%. CoVaR analysis reveals Islamic banks receive significant directional risk spillover from conventional banks but transmit substantially less contagion. These findings suggest that while Islamic banking's profit-loss sharing principles and asset-backed financing provide buffer against financial sector crises, the system remains vulnerable to real economy disruptions, challenging the prevailing narrative of unconditional Islamic banking superiority during economic turbulenceThis study investigates the comparative resilience and contagion risk profiles of Islamic banking systems during two major global economic crises: the 2008 Global Financial Crisis (GFC) and the 2020 COVID-19 pandemic. However, profitability declined significantly in 2009 when the crisis affected the real economy. Conversely, during the COVID-19 pandemic, Islamic banks exhibited comparable systemic vulnerabilities to conventional banks when facing exogenous shocks, though with significantly reduced spillover effects. CAR increased from 24.0% to 26.5% while NPF improved from 2.1% to 2.0% during COVID-19, demonstrating structural resilience despite ROA declining from 1.9% to 1.4%. These findings suggest that while Islamic banking's profit-loss sharing principles and asset-backed financing provide buffer against financial sector crises, the system remains vulnerable to real economy disruptions, challenging the prevailing narrative of unconditional Islamic banking superiority during economic turbulence